Decomposition of financial-economic indicators during probability evaluation of bankruptcy risk (for sea trade ports of Ukraine) - Нєнно, Ірина Михайлівна (Technology audit and production reserves, 2016)
The assessment of integrated sea trade ports bankruptcy risk was done with the software «Analysis of financial risks and overall risk of bankruptcy». The program calculates financial ratios and visualizes the results using range-score method in the consolidated analysis of financial condition and consolidated analysis of indicators of bankruptcy, namely: financial stability, solvency, business activity, performance evaluation of the balance sheet structure, profitability and bankruptcy probability results for the years 2012-2014. The trends of sea trade ports of Ukraine development in 2012-2014 were analyzed, particularly the calculations for indicators: assets, liabilities, sales revenue, profit from operating and financing activities, the net profit were presented. The calculations showed that for the period analyzed, there was deterioration and development of ports in 2013 while to get the positive development it became possible in 2014. The worst results in terms of probability of bankruptcy were received according to the Conan and Holder models. Only three of the ten ports showed low bankruptcy for bankruptcy probability in 2014. The differentiation in the probability evaluation results was found. In terms of Lis and Springate models significant evaluation part is the increase of capitalization, whereas according to the model of Conan Holder the importance of creating added value in the company is vital.